INCREASING THEMATIC LEARNING OUTCOMES OF ASEAN MATERIAL THROUGH COOPERATIVE LEARNING MODEL ASSISTED WITH INTERACTIVE MEDIA - Bintang Fahlia Lestari; Isna Ida Mardiyana; Astien Diena Koesmini; Rukmiyati Rukmiyati (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This Classroom Action Research, entitled efforts to improve thematic learning outcomes in Social Sciences (IPS) content on ASEAN cooperative learning models assisted by interactive media, is hoped that these learning models and media can also provide opportunities for students to discuss with friends to respect each other. The research was conducted on fourth grade students at UPTD SDN Mlajah 2 Bangkalan. The data in the study were collected using observation, interviews, documentation and tests. In this study, using 2 cycles accompanied by reflection in each cycle. Based on the analysis of the data obtained by class VI students at UPTD SDN Mlajah 2 Bangkalan, there was an increase from cycle 1 to cycle 2. In cycle 1 students obtained an average test score of 68, while in cycle 2 obtained an average test score of 82.2. Thus, students experience an increase in learning outcomes and are expected to be used as a reference for further teaching and learning processes. Thus, it can be concluded that the cooperative learning model assisted by interactive media is applied during the teaching and learning process